NITROGEN AND HUMIC ACID ACTIVATION OF ALUMOSILICATES FOR IMPROVING THE ADSORPTION OF TRITIUM FROM WATER SOLUTIONS - Pushkarev, О.; Rudenko, I.; Zubko, O.; Dolin, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The urgent problem of protecting the environment from the impact of enterprises of the fuel nuclear power complex is the search for effective means to localize tritium from industrial wastewater. In the practice of preventing environmental pollution with industrial waste, mineral adsorbents, among which a significant place is occupied by bentonite (that is, montmorillonite) and palygorskite clays and minerals from the group of zeolites (clinoptilolites and others) are widely used. To increase the adsorption capacity of mineral adsorbents, various methods for their activation are being developed. To assess the effectiveness of the activation of the adsorption capacity of such mineral adsorbents on the removal of tritium from aqueous solutions, a series of experiments was performed, where nitric and humic acids were used as activators. As a result of the work performed, it was found that acid activation increases the removal of tritium from aqueous solutions by 6% in montmorillonite and 52% in palygorskite. A further modification with humic acid, respectively, increases the removal of tritium from aqueous solutions by montmorillonite by an additional 33% (39% in total) and in palygorskite by 16% (68% in total). Activation of clinoptilolite by nitric and humic acids was not effective in increasing the extraction of tritium from aqueous solutions.
Keywords: tritium; hydrogen; heavy isotopes of hydrogen; montmorillonite; palygorskite; clinoptilolite; adsorption; fractionation